2019
DOI: 10.1089/ars.2017.7380
|View full text |Cite
|
Sign up to set email alerts
|

Critical Roles of Carbon Monoxide and Nitric Oxide in Ca2+Signaling for Insulin Secretion in Pancreatic Islets

Abstract: These results demonstrate that CO, the downstream regulator of NO, plays a role in bridging the gap between the Ca signaling messengers during insulin secretion in pancreatic β-cells. Antioxid. Redox Signal. 00, 000-000.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…It was demonstrated in pancreatic islets that CO activates CD38 through the activation of sGC. 54 Nevertheless, in platelets CO released from CORMs does not act through sGC (see Refs 11 , 12 and Figure IV in the Data Supplement ) making CO/cGMP/CD38 pathway unlikely to operate in platelets.…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated in pancreatic islets that CO activates CD38 through the activation of sGC. 54 Nevertheless, in platelets CO released from CORMs does not act through sGC (see Refs 11 , 12 and Figure IV in the Data Supplement ) making CO/cGMP/CD38 pathway unlikely to operate in platelets.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies implicated nitric oxide as the effector molecule responsible for the detrimental effects of proinflammatory cytokines on β-cell function (55,56). The role of nitric oxide in β-cell pathophysiology has been investigated over the years, and recent findings suggest its dual role as a molecule that inhibits insulin secretion but also as an activator of protective pathways, which protects β cells from damage (57,58). Our results demonstrated that overexpression of galectin 3 is related to increased levels of nitrite oxide, which is followed by its deleterious effects on β cells (Figure 5).…”
Section: Discussionmentioning
confidence: 55%
“…Potential toxicity of the free iron released by this reaction is prevented by its sequestration by ferritin, a physiological regulator of iron levels – and biliverdin is subsequently converted by biliverdin reductase to bilirubin, a potent endogenous antioxidant, which contributes substantially to control of inflammation by inhibition of NADPH oxidase [ 15 ]. CO is produced by this reaction at levels in which it acts as a highly efficient second messenger that augments cellular resistance to oxidative stress by increasing intracellular cyclic nucleotides, particularly cGMP, according to the general reaction: CO-> guanylate cyclase ->increased cGMP [ 16 ]. These HO-mediated processes additionally stabilize membrane ionic balance preventing mitochondrial calcium overload-induced tissue damage [ 17 ].…”
Section: Heme Oxygenases: Major Physiological Activitiesmentioning
confidence: 99%